Synthesis and evaluation of an amphiphilic deferoxamine:gallium-conjugated cationic random copolymer against a murine wound healing infection model of Pseudomonas aeruginosa. (May 2021) - Qiao, Jing; Liu, Zhi; Cui, Shuolin; Nagy, Tamas; Xiong, May P.
Abstract: Multidrug resistant (MDR) Gram-negative bacteria are an urgent global health threat. We report on the design and evaluation of a xenosiderophore-conjugated cationic random copolymer (pGQ-DG) which exhibits selective antibacterial activity against Pseudomonas aeruginosa ( P. aeruginosa) by targeting select outer membrane (OM) receptors for scavenging xenosiderophores such as deferoxamine (DFO), while possessing favorable cytocompatibility and exhibiting low hemolysis, to enhance and safely damage the bacterial OM. pGQ-DG demonstrated synergistic properties in combination with vancomycin (VAN) when evaluated in vitro against P. aeruginosa . In addition, pGQ-DG plus VAN cleared the P. aeruginosa infection and efficiently accelerated healing in a murine wound healing model as effectively as colistin, suggesting that this strategy could serve as an alternative to colistin against MDR bacteria. Statement of significance: P. aeruginosa exhibits intrinsic antibiotic resistance due to limited permeability of its outer membrane (OM). A triple combination antipseudomonal approach was investigated by 1) selectively targeting P. aeruginosa through the complex DFO:gallium, 2) disrupting the OM through a cationic random copolymer, and 3) enhancing bacteria sensitivity to VAN as a result of the OM disruption. Synthesis and characterization of the lead polymer pGQ-DG, mechanism of action, antimicrobial activity, and biocompatibility were investigated in vitro and in vivo . Overall pGQ-DG plus VAN cleared the P. aeruginosa infection and accelerated wound healing in mice as effectively as colistin, suggesting that this strategy could serve as an alternative to colistin against multidrug resistant P. aeruginosa . Graphical abstract: Image, graphical abstract